2021
DOI: 10.1186/s13287-021-02177-0
|View full text |Cite
|
Sign up to set email alerts
|

The angiogenic potential of CD271+ human adipose tissue-derived mesenchymal stem cells

Abstract: Background Autologous fat grafting is often a crucial aspect of reconstructive and aesthetic surgeries, yet poor graft retention is a major issue with this technique. Enriching fat grafts with adipose tissue-derived mesenchymal stem cells (AD-MSCs) improves graft survival—however, AD-MSCs represent a heterogeneous population. Selection of subpopulations of AD-MSCs would allow the targeting of specific AD-MSCs that may benefit fat graft survival more than the general AD-MSC population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
1
11
1
Order By: Relevance
“…In previous reports, CD271 + cells from BM and AT showed reduced surface CD271 expression during early in vitro passaging but maintained 0.5%–5% of CD271-expressing cells upon further passaging. 38 , 40 We confirmed that approximately 5%–10% of our sorted AT-CD271 + cells retained surface CD271 protein expression after eight passages ( Figure S3 C).…”
Section: Resultssupporting
confidence: 70%
“…In previous reports, CD271 + cells from BM and AT showed reduced surface CD271 expression during early in vitro passaging but maintained 0.5%–5% of CD271-expressing cells upon further passaging. 38 , 40 We confirmed that approximately 5%–10% of our sorted AT-CD271 + cells retained surface CD271 protein expression after eight passages ( Figure S3 C).…”
Section: Resultssupporting
confidence: 70%
“…Interestingly, previous demonstrations that CD271 + cell/HUVEC coculture, but not conditioned medium, could enhance the tube formation of HUVECs, suggest the importance of cell-to-cell interactions between CD271 + progenitors and target cells. 51,52 In our xenograft model, we observed CD271 + progenitors were surrounding capillaries and labeled by perfused lectin as with capillaries (Figure 4B-C and Figure S3A). This indicates the close proximities between "leaky" capillaries and engrafted cell grafts.…”
Section: Discussionmentioning
confidence: 68%
“…There is a report demonstrating that CD271 + progenitors secreted angiogenic factors in vitro . 52 However, limited angiogenesis was concomitantly observed in a mouse model of CD271 + cell injection for cartilage repair. 53 Based on our present results, CD271 + progenitors could exhibit angiogenic capacity specifically in ischemic-type diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the MSCs express some neural development related genes and some of them have been identified as MSC markers, such as CSPG4 (chondroitin sulfate proteoglycan 4) [228][229][230], GD2 (Disialoganglioside) [231], CD271 [232][233][234][235][236][237][238], and Nestin [239][240][241][242][243]. Whether the expression of neuron related genes indicates the dedifferentiated state of MSCs or potential interactions between MSCs and neurons remains unclear and needs further investigation.…”
Section: Neuron Related Markersmentioning
confidence: 99%